Molecular origin of viscoelasticity in mineralized collagen fibrils. (24th March 2021) - Milazzo, Mario; David, Alessio; Jung, Gang Seob; Danti, Serena; Buehler, Markus J.
Abstract : Bone is mineralized tissue constituting the skeletal system, supporting and protecting the body's organs and tissues. We unveil the molecular origins of its viscoelasticity with a full atomistic model. Abstract : Bone is mineralized tissue constituting the skeletal system, supporting and protecting the body's organs and tissues. In addition to such fundamental mechanical functions, bone also plays a remarkable role in sound conduction. From a mechanical standpoint, bone is a composite material consisting of minerals and collagen arranged in multiple hierarchical structures, with a complex anisotropic viscoelastic response, capable of transmitting and dissipating energy. At the molecular level, mineralized collagen fibrils are the basic building blocks of bone tissue, and hence, understanding bone properties down to fundamental tissue structures enables better identification of the mechanisms of structural failures and damage. While efforts have focused on the study of micro- and macro-scale viscoelasticity related to bone damage and healing based on creep, mineralized collagen has not been explored at the molecular level. We report a study that aims at systematically exploring the viscoelasticity of collagenous fibrils with different mineralization levels. We investigate the dynamic mechanical response upon cyclic and impulsive loads to observe the viscoelastic phenomena from either shear or extensional strains via molecular dynamics. We perform a sensitivity analysis with several key benchmarks: intrafibrillar mineralization percentage, hydration state, and external load amplitude. Our results show an increase of the dynamic moduli with an increase of the mineral percentage, pronounced at low strains. When intrafibrillar water is present, the material softens the elastic component, but considerably increases its viscosity, especially at high frequencies. This behavior is confirmed from the material response upon impulsive loads, in which water drastically reduces the relaxation times throughout the input velocity range by one order of magnitude, with respect to the dehydrated counterparts. We find that, upon transient loads, water has a major impact on the mechanics of mineralized fibrillar collagen, being able to improve the capability of the tissue to passively and effectively dissipate energy, especially after fast and high-amplitude external loads. Our study provides knowledge of bone mechanics in relation to pathologies deriving from dehydration or traumas. Moreover, these findings show the potential for being used in designing new bioinspired materials not limited to tissue engineering applications, in which passive mechanisms for dissipating energy can prevent structural failures.